Acute effect of a grape concentrate intake on oxidative stress markers in triathletes - Silvestre, J. C.; Ridel Juzwiak, C.; Pittelli Boiago Gollücke, A.; Zuniga Dourado, V.; D´Almeida, V. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2014)
The aim of this crossover study was to evaluate the effect of a grape concentrate (test drink [TD]) on oxidative stress markers (thiobarbituric acid reactive substances [TBARS], catalase [CAT], superoxide dismutase [SOD], and glutathione [GSH]). Six triathletes had their physical fitness, body fat composition (%BF) and food intake evaluated. Afterwards, the athletes received two doses of 300 mL of the TD (45.8g of polyphenols/kg) or a placebo drink (PL), at breakfast and after a training session (100 km of cycling, 6 km of running and 1.5 km of swimming). Blood samples (5 ml) were collected after an overnight fasting, immediately after exercise, and one hour after exercise. The triathletes presented the following characteristics (mean and standard-deviation): 43.8±10.2 years old, VO2máx 45±5.15 mL/kg/min, %BF 13.6±4.2 %, training 270.8±87.1 km/week, 3.1±1.88 hours/training/day. There was a significant increase in SOD from the 1st to the 2 nd (p=0.027) and 3 rd (p=0.02) blood tests, in response to exercise, regardless of the drink consumed. One hour after exercise, the increase in glutathione values was greater when the PL was consumed (27.5%) in relation to the TD intake (1.8%). In both tests, exercise increased TBARS values; however, when PL was consumed, subjects` values were higher (PL=2.5±1.1 nmol/ml vs. BT=1.77±1.3 nmol/ml). When PL was consumed, mean CAT values (BT=34.2±6.9 U/mgHb vs. PL=24.6±12.5 U/mgHb) reduced from the 1st to the 2 nd blood test (28.6%). TBARS, CAT and GSH values suggest that the TD presents potential to modulate exercise-induced oxidative stress